Prevalence and factors affecting the use of Tobacco, Alcohol and addictive substance among university students in Eastern Turkey - Deveci, S. Erhan; Açik, Yasemin; O?uzöncül, A. Ferdane; Deveci, Figen (SEAMEO TROPMED Network, 2010)
This study investigated the prevalence and factors affecting the use of cigarettes, alcohol and addictive substances among university students in Eastern Turkey. This cross-sectional study was conducted on 2,258 students at Firat University in the city of Elazig, eastern Turkey. The subjects were students, randomly selected from each department of the university. A questionnaire was administered to the students under direct observation. The mean age of the participants was 21.36±2.93 years. Twenty-nine point three percent of the students smoked and 26.9% used alcohol. Six point six percent declared they had used an addictive substance other than cigarettes or alcohol at least once during their lifetime. Students who smoked had a higher monthly family income and allowance than nonsmokers (p<0.05). Smoking was more prevalent among students whose fathers, siblings or close friends also smoked (p<0.05). The use of alcohol was higher among students whose close friends used alcohol (p<0.05). Six point three percent of participants stated they knew classmates who used addictive substances other than cigarettes or alcohol, and 12.4% declared they knew friends outside the classroom who used addictive drugs. At Firat University a large proportion of students reported using alcohol or smoking. Access to addictive drugs was also prevalent. Educational programs oriented towards young people must be prioritized in order to raise awareness regarding substance use.
Keywords: Addictive drugs; Alcohol; Smoking; Turkey; University students